Transivity Analysis of the “Campus Merdeka” Speech by Nadiem Makarim - Hidayat Nst; Eddy Setia; Nurlela (East Asian Journal of Multidisciplinary Research, 2022)
In this study, Nadiem Makarim's speech was analyzed about an independent campus. The data analyzed is Nadiem Makarim's speech about an independent campus in the form of a clause. This study aims to describe the speech of the Minister of Education Nadiem Makarim. This study applies a systemic functional linguistic approach (LFS) to analyze the speech of the minister of education presented by Nadiem Anwar Makarim which discusses the independent campus. The data that has been shared will be analyzed for the meaning of the process which includes (1) material processes, (2) mental, (3) relational, (4) behavioral, (5) verbal, and (6) form. Based on the results of the analysis of Nadiem Makarim's speech about the Merdeka Campus, six processes were found that represented Nadiem Makarim's experience. Of the six processes found, the most dominant process used is the material process of 43.76%. The dominant participant I used was the actor participant at 38.05%. Participant II which is dominantly used is the goal participant by 43.90%. The most dominant circumstantial used was the location circumstantial as much as 37.21%. This shows that the speech delivered by Nadiem Makarim regarding an independent campus can be realized through actions or actions taken by students, lecturers, chancellors, or people involved in higher education.